NEXUS Gains in the Ganges River Basin: India, Nepal - CGIAR Initiative on NEXUS Gains (International Water Management Institute, 2024)
A NEXUS Gains transboundary river basin brief shares examples of the Initiative’s work across five work packages in the Ganges Basin, covering India and Nepal.